Durable Marimo-like carbon support for Platinum nanoparticle catalyst in polymer electrolyte fuel cell. (20th September 2016) - Baba, Koki; Nishitani-Gamo, Mikka; Ando, Toshihiro; Eguchi, Mika
Abstract: This study deals with the electrochemical stability of carbon-based catalyst supports as the cathode material of a polymer electrolyte fuel cell (PEFC). The platinum catalyst on the carbon black supports (Pt/CB) was investigated for use in the PEFC. Marimo-like carbon (MC) was used for the catalyst support. Electrochemical surface oxidation of the Marimo-like carbon was compared to that of conventional carbon black during simulated start-stop cycles. We observed a different durability of the electrocatalytic activity between the carbon black and the Marimo-like carbon based on the CV measurements and the XPS. In case of the carbon black, the electrochemical active surface area (ECA) decreased and the electric double layer current density increased with increasing number of cycles in the accelerated degradation test (ADT). These results indicated oxidation of the carbon in the Pt/CB by the ADT. In case of the Marimo-like carbon, the ECA decreased less than in the case of the carbon black, and no change was observed in the XPS. These results indicated that surface oxidation of the Marimo-like carbon proceeded less than that of the conventional carbon black.